Cassava as livestock feed in Africa. Proceedings of a workshop - Hahn, S.K.; Reynolds, L.; Egbunike, G.N. (International Institute of Tropical Agriculture, 1992)
The aim of the workshop is to collect information on traditional African processing technologies with emphasis on cassava as a livestock feed, to review the marketing and economics of cassava by-products, to recommend strategies for future research and development on the processing and utilization of cassava as a livestock feed, and to disseminate up-to-date information on cassava. The papers in this report discusses the utilization of cassava with particular reference to farming systems, traditional processing, effect of protein deficiency on utilization and potential of cassava peels for feeding goats. The other papers looks at varietal improvement of cassava, processing of cassava, and cassava utilization in selected countries.